Covid-19: did higher trust societies fare better? - Bernard H Casey (Springer, 2023)
Abstract Social trust-between governments and people and between individuals-and trust in science were proposed as prerequisites for tackling covid. Others suggested less democratic societies were more able to impose strict rules stopping the virus. These propositions were tested for a group of mainly advanced countries. The dependent variable is cumulated deaths from covid. Findings are broken down between (a) OECD member countries, (b) these and countries having cooperation agreements with it, and (c) all these plus China. They are also broken down by time-between (a) the period before the appearance of "new variants" in late 2020 and (b) the period from then until end September 2021. The best, most parsimonious, models explain nearly half of the changes in the level of deaths. Trust in government improves outcomes, as does interpersonal trust. Vaccine antipathy does not play a role. Also, there is little indication that authoritarian regimes performed better than higher trust societies. In the first period, increasing wealth inequality-indicating a more divided society-is related to higher death rates. Hospital bed availability is important then, but not thereafter. Furthermore, as the pandemic persisted, the importance of pre-existing levels of social trust declined. The paper warns that institutions and cultures cannot easily be transferred from one country to another. Nor would all transfers be desired. It also suggests that some other lessons of what contributed to better outcomes under covid might be relevant for the monkeypox virus-its successor public health emergency.